Copolymeric Micelles Overcome the Oral Delivery Challenges of Amphotericin B - Pataranapa Nimtrakul; Desmond B. Williams; Waree Tiyaboonchai; Clive A. Prestidge (MDPI AG, 2020)
Classified as a Biopharmaceutical Classification System (BCS) class IV drug, amphotericin B (AmB) has low aqueous solubility and low permeability leading to low oral bioavailability. To improve these limitations, this study investigated the potential of AmB-loaded polymeric micelles (AmB-PM) to increase intestinal absorption. AmB-PM were prepared with polyvinyl caprolactam-polyvinyl acetate-polyethylene glycol copolymer (Soluplus®) as a polymeric carrier and used a modified solvent diffusion and microfluidics (NanoAssemblr®) method. AmB-PM have a mean particle size of ~80 nm and are mono-disperse with a polydispersity index <0.2. The entrapment efficiency of AmB was up to 95% and achieved with a high drug loading up to ~20% (w/w) with a total amount of incorporated drug of 1.08 ± 0.01 mg/mL. Importantly, compared to free drug, AmB-PM protected AmB from degradation in an acidic (simulated gastric) environment. Viability studies in Caco-2 cells confirmed the safety/low toxicity of AmB-PM. In vitro cellular absorption studies confirmed that AmB-PM increased AmB uptake in Caco-2 cells 6-fold more than free AmB (i.e., 25% compared with 4% within 30 min). Furthermore, the permeability of AmB across Caco-2 monolayers was significantly faster (2-fold) and more pronounced for AmB-PM in comparison to free drug (3.5-fold increase). Thus, the developed AmB-PM show promise as a novel oral delivery system for AmB and justifies further investigation.